2020
DOI: 10.1371/journal.pone.0224001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating HPV cDNA in the blood as a reliable biomarker for cervical cancer: A meta-analysis

Abstract: The applications of liquid biopsy have attracted much attention in biomedical research in recent years. Circulating cell-free DNA (cfDNA) in the serum may serve as a unique tumor marker in various types of cancer. Circulating tumor DNA (ctDNA) is a type of serum cfDNA found in patients with cancer and contains abundant information regarding tumor characteristics, highlighting its potential diagnostic value in the clinical setting. However, the diagnostic value of cfDNA as a biomarker, especially circulating HP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 39 publications
(49 reference statements)
1
65
0
1
Order By: Relevance
“…Another fact that has to be taken into account is that detection of cfHPV-DNA is not specific for a certain location of an HPV-related tumor. Although highly unlikely, the positivity of cfHPV-DNA can also occur due to a simultaneous second HPV-related primary other than oropharynx, as cfHPV-DNA is also reported to be a reliable biomarker for cervical carcinoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fact that has to be taken into account is that detection of cfHPV-DNA is not specific for a certain location of an HPV-related tumor. Although highly unlikely, the positivity of cfHPV-DNA can also occur due to a simultaneous second HPV-related primary other than oropharynx, as cfHPV-DNA is also reported to be a reliable biomarker for cervical carcinoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity between studies was evaluated through chi-squared and I 2 tests. Values of p < 0.1 or I 2 higher than 50% indicated the existence of significant heterogeneity [ 39 ]. Subgroup analysis was performed to explore the possibility of heterogeneity [ 49 ], whereas publication bias was assessed by Deeks’ funnel plot asymmetry test [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…HPV 16 and 18 strains have been described as related to high risk, potentially leading to cervical cancer [ 88 ]. A cervical precancerous state is characterised by changes in collar cells making them more susceptible to cervix cancer development within 10-year time span, if not treated in a timely manner [ 89 ]. A meta-analysis study showed that despite the existing heterogeneity amongst studies, HPV cDNA detection is a specific and relatively sensitive tool for cervical cancer diagnosis [ 89 ].…”
Section: Precancerous Lesions and Early Cancer Detectionmentioning
confidence: 99%
“…A cervical precancerous state is characterised by changes in collar cells making them more susceptible to cervix cancer development within 10-year time span, if not treated in a timely manner [ 89 ]. A meta-analysis study showed that despite the existing heterogeneity amongst studies, HPV cDNA detection is a specific and relatively sensitive tool for cervical cancer diagnosis [ 89 ]. Another study revealed the presence of HPV in 98.4% of tumours, being HPV16 and 18 dependent for 89.4% of cervical cancer patients detected [ 87 ].…”
Section: Precancerous Lesions and Early Cancer Detectionmentioning
confidence: 99%
“…In CC, methylation of several genes is described and the main examples are DcR1 / DcR2, hTERT, p73, p16, PTEN, E-cadherin, APC, MGMT, FANCF, BRAC1, hMLH1, RASSF1A, DAPK, TSLC1, FHIT, HIC1, RARβ, TIMP2 / TIMP3, CAV-1. As methylation markers, 5-hmC and 5-mC together with 5-foC and 5-caC draw the reversible cycle outline, and 6-mA participates in RNA methylation, especially miRNA (Gu, 2020). The silencing of the epigenetic gene through dense methylation of DNA within the CpG islands occurs in the CC associated with HPV.…”
Section: Evaluation Of Epigenetic Eventsmentioning
confidence: 99%